CONTENT AREA LITERACY APPROACH FOR TEACHERS AS AN EFFORTS TO IMPROVE STUDENT'S CRITICAL AND CREATIVE LITERATURE ABILITY - Andarwulan, Trisna; Damayanti, Galieh; Setyaningsih, Emi; Yuana, Ambayu Sofya (UPT. PKM UB, 2022)
Quality education is a major need in the era of increasingly competitive global competition. One of the government's efforts to make quality education is to increase literacy culture. The content area literacy approach (content area literacy) is the basis for implementing community service activities. Content area literacy is the ability to use reading and writing skills to study subject matter in a discipline; teach skills that “beginners” might use to understand disciplinary texts; a set of learning skills that can be generalized across content areas. Area literacy (content area literacy) requires content area teachers to develop literacy skills for their discipline as well as be confident in their ability to teach and develop content as they use these skills. This mentoring is relevant for all science content area teachers in schools, school administrators, literacy and instructional coaches, school counselors, and others interested in teaching and learning. This mentoring activity, which is a form of PMPK lecturer dedication, was carried out at SD Negeri 3 Duvet, Malang. This activity is for teachers and education personnel in the school.